Practical Considerations in Using Online Modified-Delphi Approaches to Engage Patients and Other Stakeholders in Clinical Practice Guideline Development - Khodyakov, Dmitry (Patient, 2019)
Patients and caregivers are increasingly recognized as key stakeholders in developing clinical practice guidelines (CPGs). Online engagement approaches offer the promise of a rigorous, scalable, and convenient engagement method. This paper illustrates how an online modified-Delphi approach could be used to engage patients, caregivers, and other stakeholder in CPG development. It provides practical guidance for conducting online modified-Delphi panels that covers (1) joint development of the engagement approach with relevant stakeholders, (2) adaptation of methods used by experts in guideline development, (3) pilot testing, (4) participant recruitment, (5) determining panel size and composition, (6) building participant capacity, (7) facilitation of two-way interaction, (8) continuous engagement and retention of participants, (9) rigorous data analysis, (10) evaluation of engagement activities, and (11) result dissemination. The paper is based on a recently completed study about engaging individuals with Duchenne muscular dystrophy (DMD) and their caregivers in determining the patient-centeredness of DMD care guidelines.